A novel approach to identify responder subgroups and predictors of response to low‐ and high‐dose capsaicin patches in postherpetic neuralgia. (6th May 2013) - Martini, C.H.; Yassen, A.; Krebs‐Brown, A.; Passier, P.; Stoker, M.; Olofsen, E.; Dahan, A.
Abstract Background Treatment of chronic pain conditions is commonly assessed at specific endpoints at preset times during or after treatment by analysis of the total study population. An alternative approach is the identification of specific patient subgroups characterized by differential response patterns in their analgesic response and to determine the presence of significant predictors of effect. Methods Data from four double‐blind, randomized controlled trials on the efficacy of topical capsaicin 8% (Qutenza) versus an active control (capsaicin 0.04%) in patients with postherpetic neuropathic pain were combined. Longitudinal pharmacodynamic, mixture and covariate analyses were performed on the pooled dataset. Results Data from 1248 patients treated with Qutenza (n = 722) or topical low‐dose capsaicin 0.04% (n = 526) were successfully analysed. Five distinct response subgroups were detected with different treatment efficacies, including a group of non‐responders, a group showing partial analgesic effect and a group showing full analgesic effect. Active control and Qutenza had similar response profiles, but the proportional distribution of patients among the five response groups was in favour of Qutenza, with 40% less non‐responders and 25% more patients showing a full analgesic response. For Qutenza, important predictors of efficacy were efficacy of lidocaine pretreatment and greater pretreatment pain score variability. Conclusions The analyses indicate the existence of different response groups to treatment with Qutenza and an active control patch that may possibly be related to different pain mechanisms among these groups, despite a presumed common underlying disease process, and that require different treatment approaches among subgroups.